2017
DOI: 10.1080/16546628.2017.1325307
|View full text |Cite
|
Sign up to set email alerts
|

Effects of epigallocatechin-3-gallate on thermogenesis and mitochondrial biogenesis in brown adipose tissues of diet-induced obese mice

Abstract: Background: Epigallocatechin-3-gallate (EGCG) is the major polyphenol in green tea and has been considered a natural agent that can help to reduce the risk of obesity.Objective: The aim of this study was to investigate the effects of EGCG on thermogenesis and mitochondrial biogenesis in brown adipose tissue (BAT) of diet-induced obese mice.Methods: Male C57BL/6J mice were provided a high-fat diet for 8 weeks to induce obesity, following which they were divided into two groups: one on a high-fat control diet an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 45 publications
5
55
0
Order By: Relevance
“…However, there is limited evidence regarding the direct role of green tea components in modulation of metabolic diseases such as obesity and diabetes, as EGCG has been the major focus of investigation. A recent study examining the effects of EGCG on 3T3‐L1 adipocytes demonstrated results similar to those of the present study regarding the adipocyte differentiation marker UCP1 . Other studies have shown that high EGCG concentrations cause decrease in peroxisome proliferator‐activated receptor gamma and adiponectin expression, along with a reduction in cell number .…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…However, there is limited evidence regarding the direct role of green tea components in modulation of metabolic diseases such as obesity and diabetes, as EGCG has been the major focus of investigation. A recent study examining the effects of EGCG on 3T3‐L1 adipocytes demonstrated results similar to those of the present study regarding the adipocyte differentiation marker UCP1 . Other studies have shown that high EGCG concentrations cause decrease in peroxisome proliferator‐activated receptor gamma and adiponectin expression, along with a reduction in cell number .…”
Section: Resultssupporting
confidence: 89%
“…A recent study examining the effects of EGCG on 3T3-L1 adipocytes demonstrated results similar to those of the present study regarding the adipocyte differentiation marker UCP1. [17] Other studies have shown that high EGCG concentrations cause decrease in peroxisome proliferator-activated receptor gamma and adiponectin expression, along with a reduction in cell number. [20] However, viability of both 3T3-L1 preadipocytes and adipocytes was decreased by exposure to high concentrations of EGCG.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Plant‐based bioactive compounds from fruits and vegetables have been found to inhibit lipogenesis while promoting brown and beige adipocyte development and thermogenesis and are therefore considered novel nutritional intervention strategies in the prevention of obesity and its related chronic diseases. Mechanisms underlying the anti‐obesogenic activities of some polyphenols, including epigallocatechin gallate, resveratrol, quercetin, and curcumin have been investigated in in vitro, in vivo, and human clinical studies. While anti‐inflammatory and anti‐cancer activities of polyphenols such as GTs and their derivatives (GA and PG) have been examined in breast cancer and colitis models, investigation of these polyphenols in obesity seems to be limited.…”
Section: Discussionmentioning
confidence: 99%
“…EGCG is one of the most abundant and potent polyphenols in green tea. As with other polyphenolic compounds, EGCG has been studied for its antioxidant, anti-inflammatory, and anti-obesity effects [ 135 , 136 , 137 ]. When treated with EGCG for 16 weeks, mice placed on a HFD and 10% fructose solution resisted obesity development and displayed better CNS insulin sensitivity than HFD-fed obese control mice [ 138 ].…”
Section: Role Of Antioxidants/anti-inflammatory Agents In the Cnsmentioning
confidence: 99%